2003
DOI: 10.1507/endocrj.50.459
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Study of Thyrotropin Releasing Hormone (TRH) Receptor Using RT-PCR: Relationship to Clinical and Immunohistochemical Phenotypes in a Series of Human Pituitary Adenomas

Abstract: Abstract. Thyrotropin releasing hormone receptor 1 (TRHR1) and 2 (TRHR2) mRNAs were examined using reverse transcription polymerase chain reaction (RT-PCR). These data were then correlated with endocrinological and histological characteristics in 65 human pituitary adenomas including one non tumorous pituitary gland, to clarify the role of TRHR1 and 2 gene expression in human pituitary adenomas, especially as it relates to the paradoxical stimulatory effects of TRH found in pituitary adenomas. TRHR mRNA was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, ectopically expressed TRH receptors cross-couple with cAMP and regulate GH secretion by somatotroph cells (34), and the abnormal GH response is more frequently observed in adenomae with gsp mutation than those without the mutation (35) as is in our series. As gsp mutation was more frequently encountered in non-DP adenomae in this study, it is thus rational to expect TRH receptor prevailed more frequently in DG GHomae than in SG ones (31). Ectopic expression of TRH receptors may couple with tumourigenesis of GHomae (triggered by gsp mutation) and amplified cAMP signalling (36,37).…”
Section: Ck Staining Patterns and Clinico-pathological Featuresmentioning
confidence: 65%
See 1 more Smart Citation
“…However, ectopically expressed TRH receptors cross-couple with cAMP and regulate GH secretion by somatotroph cells (34), and the abnormal GH response is more frequently observed in adenomae with gsp mutation than those without the mutation (35) as is in our series. As gsp mutation was more frequently encountered in non-DP adenomae in this study, it is thus rational to expect TRH receptor prevailed more frequently in DG GHomae than in SG ones (31). Ectopic expression of TRH receptors may couple with tumourigenesis of GHomae (triggered by gsp mutation) and amplified cAMP signalling (36,37).…”
Section: Ck Staining Patterns and Clinico-pathological Featuresmentioning
confidence: 65%
“…In this study, the incidence of abnormal response to preoperative TRH or LHRH challenge test was significantly (P!0.05) lower in DP adenomae than in non-DP adenomae. Ectopic TRH receptors in GHomae cells play an important role in the abnormal GH response to TRH (31). Physiologically, TRH receptors act via the inositol 1,4,5-triphosphate pathway to release TSH and PRL (32,33).…”
Section: Ck Staining Patterns and Clinico-pathological Featuresmentioning
confidence: 99%
“…A paradoxical TRH test in acromegaly is considered as non-diagnostic and thus clinically not useful, because it can be also present in other conditions, such as in children, anorexia nervosa, and serious liver disease [155]. Interestingly, acromegalic patients with a paradoxical response of GH to TRH express the TRH receptor in the adenoma, while TRH-negative patients do not [156], establishing the pathophysiological basis for this response. In a selected series of acromegalic patients who had a normal postoperative GH suppression (although differing in magnitude) and a normalized TRH test, only one recurrence was noted after a 14.3 years [160].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Liu et al (2009) is pointed by the catalog of the National Human Genome Research Institute (Hindorff et al 2010) as the only work that found the association of TRHR gene and body mass (lean). Until then, studies with this gene were associated with other outcomes such as pituitary adenoma (Igarashi-Migitaka et al 2003) and hypertension (GarcĂ­a et al 2001;Ruixing et al 2008).…”
Section: Discussionmentioning
confidence: 99%